CLASH-VLT: constraints on the dark matter equation of state from accurate measurements of galaxy cluster mass profiles - Sartoris, Barbara; Bartelmann, Matthias (Arxiv, 2014)
A pressureless scenario for the Dark Matter (DM) fluid is a widely adopted hypothesis, despite the absence of a direct observational evidence. According to general relativity, the total mass-energy content of a system shapes the gravitational potential well, but different test particles perceive this potential in different ways depending on their properties. Cluster galaxy velocities, being $\ll
Gesehen am 20.09.2017